The Effect of Using the Canva Application on Social Science Learning Outcomes of Class VII Students of Upt UPT SMP Negeri 3 Pitu Riase - Rahmawati, Rahmawati; M, Usman; Takdir, Muhammad; Hermansyah, Sam; Barroso, Uwe; Intes, Amina (Journal International Inspire Education Technology, 2023)
Abstract— This This study uses a quantitative method with the type of experimental research that aims to testThe Effect of Using the Canva Application on Social Science Learning Outcomes of Grade VII Students of UPT SMP Negeri 3 Pitu Riase.The population is 29 students with sampling technique using saturated sampling or total sampling. There are 2 variables in this study, namely the independent variable The Effect of Using the Canva(X) Application and the dependent variable, namely Social Science Learning Outcomes of Class VII Students of SMP Negeri 3 Pitu Riase (y). This research was conducted at UPT SMP Negeri 3 Pitu Riase.Data collection techniques using documentation and tests. The collected test results data were analyzed using the mean formula. Based on the results of data analysis, it was obtained that the value of X = 75.53> the value of Y = 67.71 so that it can be seen that there is an effect of using the Canva application on the learning outcomes of Class VII students of SMP Negeri 3 Pitu Riase.Based on the research results obtained, it can be concluded that the Effect of Using the Canva Application on the Social Science Learning Outcomes of Class VII Students of SMP Negeri 3 Pitu Riase, this shows that the working hypothesis states that There is an Effect of Using the Canva Application on Social Science Learning Outcomes of Class VII UPT Students SMP Negeri 3 Pitu Riase,accepted